Laparoscopic excision of neurogenic retrorectal tumors. Issue 2 (May 2017) - Manabe, Tatsuya; Koba, Ryo; Nagayoshi, Kinuko; Sadakari, Yoshihiko; Fujita, Hayato; Nagai, Shuntaro; Ueki, Takashi; Nagai, Eishi; Nakamura, Masafumi
Abstract: Retrorectal tumors (RT) are uncommon and usually managed by open surgical excision. Laparoscopic excision for RT has been reported in only a small number of papers. We aimed to assess the laparoscopic approach for RT and to discuss the factors that made this procedure difficult. We performed laparoscopic excision using a five‐trocar technique for neurogenic RT in three patients. Tumors were successfully excised laparoscopically in two patients. However, the third patient required open conversion because the tumor was strongly adhered to the sacrum and could not be mobilized by dissection, resulting in poor visualization of the dissected site. Laparoscopic excision for RT provides excellent intraoperative visualization and good cosmesis in selected patients, but firm adherence to the sacrum may cause difficulty with this procedure.